2003
DOI: 10.1177/1420326x03012003004
|View full text |Cite
|
Sign up to set email alerts
|

Species of Conditionally Pathogenic Micromycetes in the Air of Dwellings and Occupational Premises

Abstract: The spread of filamentous fungi in occupational premises and dwellings predetermines not only the pollution of the surroundings, but also influences the health of their occupants. Problems caused by micromycetes are of major importance in Lithuania where, because of the climatic conditions, people spend a large part of their time indoors. Over the years 1994-2000 the microbiological state of various dwellings and occupational premises in Vilnius city has been investigated. Some 359 fungal species ascribed to 1… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
9
0

Year Published

2006
2006
2016
2016

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 16 publications
(12 citation statements)
references
References 12 publications
0
9
0
Order By: Relevance
“…Certain genera produce 3-8 different mycotoxins. Cladosporium genus fungi are mostly regarded as phylloplane organisms but certain species produce toxic substances -harmful to birds, horses and, occasionally, to humans [13]. Moreover, it was proved that the dose of mycotoxin required to cause health effect is usually one order of magnitude lower when taken by the airways than by digestive system [17].…”
Section: Discussionmentioning
confidence: 99%
“…Certain genera produce 3-8 different mycotoxins. Cladosporium genus fungi are mostly regarded as phylloplane organisms but certain species produce toxic substances -harmful to birds, horses and, occasionally, to humans [13]. Moreover, it was proved that the dose of mycotoxin required to cause health effect is usually one order of magnitude lower when taken by the airways than by digestive system [17].…”
Section: Discussionmentioning
confidence: 99%
“…Acremonium , Alternaria , Aspergillus , Cladosporium , Fusarium , Paecilomyces , Penicillium , Stachybotrys and Trichoderma are well known mycotoxin producers [48]. Aspergillus flavus and Aspergillus fumigatus can lead to aspergillosis [49], and Microsporium and Trichophyton are agents of dermatophytoses [50]. As the potential implications of the fungal contamination on health have not been studied in Egypt, it should to be reported that exposure to such concentrations and types is a risk factor for resident’s respiratory symptoms.…”
Section: Discussionmentioning
confidence: 99%
“…Fungi -Fungal strains which are proportionally of importance in indoor air samples are comprised of the genera Alternaria, Aspergillus, Cladosporium, and Penicillium [121][122][123][124][125][126]. All fungal strains are able to form spores which are resistant to changing environmental conditions.…”
Section: Composition Of Bioaerosolsmentioning
confidence: 99%